(untitled) (Research, Society and Development, 2023)
Measles is an exanthematic disease, characterized by the occurrence of symptoms such as fever and maculopapular rash, and may be associated with these coughs, runny nose and conjunctivitis. It is a notifiable disease, which is essentially prevented by vaccination. Despite this fact, there is a constant decrease in vaccination in Brazil. Thus, the objective of this study was to conduct an integrative literature review in the SciELO, PubMed and VHL databases, using the descriptors the words: "measles", immunization", "public health" and "Brazil", in order to analyze the status of measles vaccination coverage, and understand what are the factors that interfere with the success of disease prevention campaigns. As a result, 93 articles were found, so that after analysis, according to the established inclusion criteria, 8 articles were selected for the sample of this study. The selected articles show that there was a considerable decrease in measles vaccination rates, so that the analyses varied according to the time frame described in each study. The findings demonstrate that strategies are needed to increase vaccination coverage against measles, especially with regard to vaccine hesitation by the population, which influences their adherence to the vaccine. Moreover, it was evident how socioeconomic disparities also impact vaccination coverage rates. It can be concluded, therefore, that the theme besides pertinent is quite current, so that the resurgence of measles is characterized as a public health problem.